(untitled) (Globalization and Business, 2018)
This study researches the problems of Georgia›s monetary-fiscal policy and economic growth, in particular the main indicators of economic growth assessment, certain aspects of monetary, credit, currency, and investment policies; The process of tax reforms in Georgia, including changes in income tax administration, considering the Estonian model, in which entrepreneurs will be exempt from profit taxes if they reinvest part of undistributed profits (dividends); It is analyzed in this study EU-Georgia Association Agreement signed in Brussels (27.06.2014)one of the most important parts of which is an agreement about the Deep and Comprehensive Free Trade Area, which envisages liberalization of trade with the EU; The focus is on the low level of competitiveness of the private sector in Georgia, inadequate human capital and deficient financial resources, undeveloped infrastructure and measures to be taken in this direction.